Can Cr(iii) substitute for Al(iii) in the structure of boehmite?. Issue 109 (14th November 2016) - Chatterjee, Sayandev; Conroy, Michele A.; Smith, Frances N.; Jung, Hee-Joon; Wang, Zheming; Peterson, Reid A.; Huq, Ashfia; Burtt, David G.; Ilton, Eugene S.; Buck, Edgar C.
Abstract : Cr(iii ) is observed to prefer (near-)surface sites in boehmite, as opposed to the bulk. Abstract : The dissolution of boehmite is a technical issue for Al industry because of its recalcitrant nature. In fact, a similar problem exists with boehmite in nuclear waste sludge at the Hanford site in Eastern Washington State, USA. Dissolution of Al phases is required to reduce the waste loadings in the final borosilicate glass waste form. Although not the most common Al-bearing species in the sludge, boehmite may become a rate limiting step in the processing of the wastes. Hanford boehmite is an order of magnitude more resistant to dissolution in hot caustic solutions than expected from surface-normalized rates. We are exploring potential intrinsic and extrinsic effects that may limit boehmite reactivity; one clue comes from microstructural analyses that indicate an association of Cr with Al in the Hanford nuclear waste. Hence, in this first paper, we investigated the potential role of chromium on the reactivity of boehmite in caustic solution. An important finding was that irrespective of the synthesis pathway, amount of Cr(iii ), or the resultant morphology, there was no evidence for Cr incorporation in the bulk structure, in agreement with QM calculations. In fact, electron microscopic (EM) and spectroscopic analyses showed that Cr was enriched at the (101) edges of the boehmite. However, Cr had no measurable effect on the morphology during the synthesis step. In contrast, comparison of the morphologies of the synthetic Cr-doped and pure boehmite samples after exposure to caustic solutions provided evidence that Cr inhibited the corrosion. TEM showed that Cr was not homogeneously distributed at the surface. Consequently, Cr may have partially passivated the surface by blocking discrete energetic sites on the lateral surfaces of boehmite.